FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PERAWAT PADA MASA PANDEMI COVID-19 : LITERATURE REVIEW - Annisa Rahmi Galleryzki; Sefti Wahyu Lestari; Sekarini (2022)
The Covid-19 pandemic has impacted all aspects around the world. The high mortality and morbidity rates during this pandemic require nurses to provide comprehensive and quality nursing services. To achieve good service quality, good performance is needed by all nurses. Objective: to determine the factors related to the performance of nurses during COVID-19. The method used is a literature review with Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Articles are obtained from databases and search engines, Google Scholar, Science Direct, and Scopus. The Population inclusion criteria were nurses in hospitals, speaking Indonesian and English, published between 2020-2022. The keywords for the Indonesian search are â€Kinerja Perawatâ€ and â€œPandemiâ€ or COVID-19, while the English keywords are â€œnurse performanceâ€ and â€œpandemicâ€ or COVID-19â€. The obtained 534 articles and in the final stage 18 articles are obtained. Results: two main factors that affect the performance of nurses are internal and external factors. Internal factors include the motivation of nurses, commitment to the organization as well as intelligence and knowledge. While external factors are work stress, incentives/awards, workload, work environment, and leadership. Suggestion: to maintain good quality nursing services during COVID-19, good support is needed from workplace agencies as the main external factor in order to increase the commitment, motivation, and performance of nurses in carrying out their roles.